The Furniture Arrangement Study in Housing Type 21m2 - D. Agustin; N. Anggriani; E. Djuni (Nusantara Science and Technology Proceedings)
The construction of simple 21 m2 houses was built by developers, especially in big cities. At 21 m2 type houses there is very limited space. To arrange the space in it, especially arranging furniture is very difficult because of the limitations of space where residents must be able to use space optimally but still comfortable and can accommodate all the activities of its residents. This study aims to determine the arrangement of furniture in type 21 m2 houses and the factors that influence them. The resulting output is expected to be able to provide recommendations on the arrangement of simple houses of type 21 m2. This study uses a behavioral approach with quantitative non-parametric data collection which is then analyzed qualitatively. From the analysis it was found that most of the 21 m2 occupants had made changes to space zoning accompanied by additional furniture. Type 21m2 house is a residence that prioritizes space effectiveness and efficiency by integrating the results of the calculation of broad needs in each space by assuming various possible movements, structuring the right furniture that fits the zone and its needs. Comfort for occupants of type 21 m2 houses can be achieved, among others, with enough space for activity, lighting and airing. Good lighting and ventilation can be adjusted to the size and function of space. Sufficient space for movement can be realized by arranging furniture and good circulation.